العزوف على المنصات التعليمية الرقمية و انعكاسها على المكتسبات العلمية لدى الطالب - ميزات محمد; بن نيش حليمة; د/ طريف عطاالله (جامعة عمار ثليجي الاغواط, 2024)
ملخص الدراسة: هدفت دراستنا الحالية لمعرفة مدى تقبل الطالب الجامعي للمنصات التعليمية الرقمية وتحديد العوامل المؤثرة في ذلكعلى عينة من طلبة كلية العلوم الانسانية والعلوم الاسلامية والحضارة بجامعة عمار ثليجي بالأغواط، كما أن الدراسة تهدف أيضا إلى دراسة مدى تأثير عزوف الطلاب عن استخدام المنصات التعليمية الرقمية على مكتسباتهم العلمية . تم تطبيق أداة الدراسة المتمثلة في الاستبيان على عينة متكونة من 78طالب وطالبة، وتم استخدام المنهج الوصفي التحليلي. وبعد جمع بيانات الدراسة تم تحليل هذه النتائج التي نلخصها فيما يلي:  وجود اختلاف في وجهات نظر الطلاب حول هذا التأثير، حيث كانت النسب متقاربة بين الموافقين والغير موافقين على بعض النقاط. ومع ذلك، أدرك غالبية الطلاب (74.35%) أهمية المنصات التعليمية الرقمية في اكتساب المعارف والمهارات بشكل أفضل، مما يشير إلى أن العزوف عنها قد يؤثر سلباً على مكتسباتهم العلمية.  تقبل جيد للمنصات التعليمية الرقمية من قبل الطلاب الجامعيين، حيث أن 76.92% على دراية بوجودها، و71.79% يستخدمونها بشكل متكرر، و66.66% يرونها توفر تجربة تعليمية أكثر فعالية.  المشكلات التقنية المتعلقة بالإنترنت، مثل ضعف الاتصال وبطء السرعة، تشكل عائقًا رئيسيًا أمام استخدام الطلاب للمنصات التعليمية الرقمية، حيث واجهت غالبية الطلاب (58.97%) مشكلات في الاتصال بالإنترنت، و76.92% واجهوا بطء سرعة الإنترنت، مما قد يؤدي إلى عزوفهم عن هذه المنصات.  اختلاف في وجهات نظر الطلاب حول هذا التأثير، ولكن غالبيتهم أدركوا أهمية هذه المنصات في اكتساب المعارف والمهارات بشكل أفضل، مما يشير إلى أن العزوف عنها قد يؤثر سلباً على مكتسباتهم العلمية. وتم تفسير النتائج وفق نتائج الدراسات السابقة، والتراث النظري المعتمد في فصول البحث الأولى. الكلمات المفتاحية: المنصات الرقمية، المكتسبات العلمية، الطالب الجامعي. Abstract: Our current study aimed to understand the university students' acceptance of digital educational platforms and to identify the factors affecting this acceptance, using a sample of students from the Faculty of Humanities and the Faculty of Islamic Sciences and Civilization at Amar Telidji University in Laghouat. The study also aimed to examine the impact of students' reluctance to use digital educational platforms on their academic achievements. A questionnaire was administered to a sample consisting of 78 students. We used the descriptive analytical method. After collecting the study data, we analyzed the results, which are summarized as follows:  There is a variation in students' perspectives on this impact, with similar percentages of agreement and disagreement on some points. However, the majority of students (74.35%) recognized the importance of digital educational platforms in better acquiring knowledge and skills, indicating that reluctance to use them may negatively affect their academic achievements.  There is a good acceptance of digital educational platforms among university students, with 76.92% being aware of their existence, 71.79% using them frequently, and 66.66% seeing them as providing a more effective learning experience.  Technical problems related to the internet, such as poor connection and slow speed, are a major obstacle to students' use of digital educational platforms. The majority of students (58.97%) faced connection issues, and 76.92% faced slow internet speeds, which may lead to their reluctance to use these platforms.  There is a variation in students' perspectives on this impact, but the majority realized the importance of these platforms in better acquiring knowledge and skills, indicating that reluctance to use them may negatively affect their academic achievements. The results were interpreted in accordance with previous studies and the theoretical framework presented in the initial chapters of the research. Keywords: Digital platforms, Academic achievements, University student.
دراسة ميدانية على عينة من طلبة كلية العلوم الانسانية و الاسلامية و الحضارة بجامعة عمار ثليجي الاغواط